Analisis Pendapatan Usahatani Padi (Oryza Sativa) Di Lahan Sub Optimal (Studi Kasus: Lahan Kering Di Kecamatan Jerowaru Kabupaten Lombok Timur) - Mustar Mustar; Muhammad Joni Iskandar; Rini Endang Prasetyowati; Muhammad Anwar (Universitas Khairun, 2025)
Suboptimal land use for food availability is unavoidable, alternative rice farming in dry land is the current choice. The fluctuating prices of agricultural production factors require an in-depth study of detailed price estimates and allocations. The purpose of this study is to analyze the income of dry land rice farming in Jerowaru District. The study is descriptive, with purposive location selection, in a dry land rice agro-ecosystem with rain-fed irrigation in Sekaroh Village, Jerowaru District, East Lombok Regency. Respondents were determined by quota sampling of 30 people and selected randomly. Data were collected using observation techniques, structured interviews, and documentation, then analyzed using cash flow analysis techniques and described using descriptive methods. The results of the study obtained the production cost components of dry land rice farming amounted to Rp12,479,222/LLG or Rp14,321,187/ha, dry grain production harvested 4,519 tons, land productivity capacity reached 1.32 ku/LLG or 1.72 ku/ha. The farm income value is Rp25,649,000/LLG or Rp29,373,500/ha. The study concluded that the income from dryland rice farming in Jerowaru District is Rp13,169,778/LLG or Rp15,052,313/ha.